Perlindungan Konsumen bagi Warga Negara Asing di Indonesia: Analisis Yuridis dan Sosiologis - Adinda Marsha; Najwa Nur; Ahmad Azmi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Consumer protection is an important pillar in ensuring fairness and balance in the relationship between business actors and consumers, including for foreign nationals who transact in Indonesia. Economic globalization and digital developments are expanding the range of cross-border economic activities that demand the presence of an inclusive legal protection system that is adaptive to modern trade dynamics. This research aims to analyze consumer protection for foreign nationals in Indonesia through juridical and sociological approaches to understand the implementation of legal norms, the effectiveness of dispute resolution mechanisms, and the social realities faced by foreign consumers in practice. The research method used is normative legal research with a legislative approach and a sociological approach through the analysis of the literature, regulations, and empirical findings from various studies related to cross-border consumer protection. The results of the study show that although normatively Law Number 8 of 1999 concerning Consumer Protection guarantees equal rights for all consumers, in practice there are still administrative, cultural, linguistic, and information access obstacles experienced by foreign citizens. These findings affirm the importance of harmonizing consumer protection policies with the principles of global justice, accessibility, and non-discrimination.